Rosiglitazone enhances neovascularization in diabetic rat ischemic hindlimb model - Khazaei, Majid; Salehi, Ensieh (Biomedical papers, 2012)
Background: There is increasing evidence that peroxisome proliferator-activated receptors (PPARs) may be involved in the regulation of angiogenesis. In this study, we examined whether rosiglitazone, a PPARγ agonist, can restore angiogenesis in a rat hindlimb ischemia model of diabetes.Methods: Male wistar rats were divided into four groups (n=6 each): control, diabetic and control and diabetic rats who received rosiglitazone (8 mg/kg/day). Diabetes was induced by streptozotocin (55 mg/kg; ip). After 21 days, serum concentrations of nitric oxide (NO), vascular endothelial growth factor (VEGF) and soluble VEGF receptor-2 (VEGFR-2) were measured and neovascularization in ischemic legs was evaluated by immunohistochemistry.Results: Capillary density and capillary/fiber ratio in hindlimb ischemia of diabetic animals were significantly lower than the control group (P<0.05). Rosiglitazone significantly restored neovascularization in diabetic animals (P<0.05).Conclusions: rosiglitazone enhances neovascularization in diabetic ischemic skeletal muscle and could be considered for treatment of peripheral artery disease in diabetic subjects.
Keywords: diabetes; rosiglitzone; angiogenesis; hindlimb ischemia